Alicyclobacillus acidoterrestris : Resistência a sanitizantes industriais, multiplicação e produção de biofilme - Anjos, Márcia Maria dos (2013)
Genus Alicyclobacillus spp. is composed of gram positive bacilli with cyclic fatty acids as the main component of the cell membrane. The forming spores are the main factors of resistance to the thermal processes in food. Growth pH ranges between 2.2 and 6.0 and temperature lies between 35ºC and 55ºC. Bacteria may change the sensorial characteristics of food, such as citric juices, since they produce guaiacol (2-methoxyphenol) providing unpleasant smell and taste to the products. These microorganisms are often associated to the degradation of reconstituted orange juice. In fact, it is unavoidable that fruits bear the bacterium or its spores to the respective industrial processes since the genus is widely distributed in the soil. Orange juice is the only Brazilian product that makes up 50% of world production and 85% of Brazilian exports. Consequently, it contributes significantly towards the country´s commercial balance; its deterioration brings high liabilities. Due to different pH bands and best temperatures for the growth of different species, it is currently difficult to identify a standard methodology for the development of Alicyclobacillus spp. In the case of bacteria control in the industrial juice processing, the industry employs procedures, such as fruit washing, aspersion by sanitizing products and pasteurization of the product. However, spores and biofilm resist all these procedures and the bacterium may nevertheless be present in the final product. Certain factors, such as concentration and contact time between sanitizing products and the microorganism, reduce the bacteria, but no conclusive data are extant on the activities of the sanitation products used in fruit washing on the spores and on the biofilm of Alicyclobacillus spp.